2008
DOI: 10.4161/cc.7.1.5111
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc protein is degraded in response to UV irradiation

Abstract: The c-MYC proto-oncogene encodes a transcription factor that is critical for cell growth and proliferation. It is one of the genes frequently altered in cancer cells in which it exhibits constitutive activity. The half-life of c-MYC is very short in quiescent cells due to ubiquitin-mediated proteolysis. We report here the rapid and dose-dependent decline of c-MYC protein level after UV-irradiation in various human and rodent cells. This decline is due to a proteasomal degradation of c-MYC protein and does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 66 publications
2
15
0
Order By: Relevance
“…We and others have shown that Myc levels are controlled by miR-34 (21,26). Although it has been shown previously that levels of Myc are reduced following DNA damage by a number of different mechanisms, including changes in the rate of transcription and protein turnover (27)(28)(29), the possible involvement of miRNAs has not been investigated. It was therefore timely to investigate the role of miR-34c in the control of Myc repression following DNA damage and its importance in this process.…”
Section: Discussionmentioning
confidence: 94%
“…We and others have shown that Myc levels are controlled by miR-34 (21,26). Although it has been shown previously that levels of Myc are reduced following DNA damage by a number of different mechanisms, including changes in the rate of transcription and protein turnover (27)(28)(29), the possible involvement of miRNAs has not been investigated. It was therefore timely to investigate the role of miR-34c in the control of Myc repression following DNA damage and its importance in this process.…”
Section: Discussionmentioning
confidence: 94%
“…For this reason, c-Myc should be tightly controlled under stress conditions. Indeed, it has recently been shown that c-Myc levels are reduced in cells following DNA damage (6,7,48). However, whether and how c-Myc is regulated in response to ribosomal stress are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, under normal circumstances these mRNAs are not efficiently translated. 88,89 However, upon Akt-mediated activation of mTOR, these latter mRNAs are highly and disproportionately translated; several key proteins that are overexpressed as a consequence of this event include c-myc, [90][91][92][93][94][95][96] cyclin D1, 97,98 and VEGF 99 among others. 88,89 Cyclin D1 has been reported to be overexpressed in CaP xenografts and metastases, 100,101 while early stage prostatic lesions possess much lower levels of the protein.…”
Section: Central Role Of Pi3k/pten/akt/mtor Pathway In Prostate Cancermentioning
confidence: 99%